Sosialisasi dan implementasi perangkat pembelajaran matematika dalam mendukung keterampilan abad 21 - I Nyoman Sridana; Arjudin Arjudin; Amrullah Amrullah; Muhammad Turmuzi; Junaidi Junaidi (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
Abstract Lack of knowledge in a number of teachers who are not able to operate the concept of learning well, namely teachers only rely on learning methods and strategies on the handbook or documents that have been received. The impact of learners has difficulty in solving problems. By utilizing the results of research on the development of mathematical learning tools in the form of teaching materials, LKPD, and RPP based on 21st century skills that are feasible to be used can solve the problem. Therefore, it is necessary to socialize and implement the results of the research to the community, especially teachers in junior high schools. the outer target of this agility is the understanding for teachers of 21st century skill-based learning tools, particularly mathematics and other subjects.